The integrated economic-geographical analysis of the Greater Poland voivodeship (Poland) and the Cherkasy region (Ukraine) - Braslavska, Oksana; Нerasymenko, Oksana (Human Geography Journal, 2019)
The integrated regional economic-geographical analysis of the Greater Poland Voivodeship (Poland) and the Cherkasy region (Ukraine) according to M. Baransky's scheme were done in the article. The economy and population of the regions were analyzed using such research methods: comparative, historical, statistical, economic zoning, remote monitoring. The most significant features of similarity and differences in economic use were determined in the article.The literature has yet to conduct a comprehensive comparative study of the regions of Poland and Ukraine, in particular, the Cherkasy region with the Polish provinces. So, we have investigated that the Greater Poland Voivodeship belongs to the strongest regions of Poland. This estimate is based on the following indicators: the size of the region, the population, including employment, the rate of GDP growth and its share per inhabitant, the level of industrial development, the pace of transformation, the dominant role of the private sector in the economy. An analysis of these indicators, conducted at the Institute for Market Economy Studies, shows that the Greater Poland is in the leading group of the best regions of the country. Cherkasy region belongs to agrarian-industrial regions of Ukraine.Based on results of the conducted research the following conclusions have been made: The formation of a civil society opens up broad preconditions for the development of industry and commodity products. Improving the assessment of social and economic development indicators, which was conducted in six areas: Financial self-sufficiency, Infrastructure development, Investment development and foreign economic cooperation, Labor market efficiency, Renewable energy and energy efficiency, and Economic efficiency about democratic progress and increase of investment attractiveness of the region. Study of comparative characteristics of socio-economic progress of regions of Ukraine and regions of Poland.